A Jewish heart: the struggle for status and identity in Asia - Green, Robert L. (Lexington Books, 2024)
"This book offers new insights into the struggles, dreams, and disappointments of Hong Kong's end-of-an-era Jewish community following an unimagined windfall and change of sovereignty, paralleled by the birth and growth of Progressive Judaism in Asia"--